PREFERENSI KONSUMEN PADA UMKM KERIPIK TEMPE DI PASURUAN - Khasanah, Nur; Nuswardhani, Sri Karuniari (Universitas Panca Marga, 2024)
ABSTRACTThis research aims to determine consumer characteristics, consumer preferences for tempeh chips products in MSMEs in Pasuruan, specifically in Ibu Nur Jannah in Urip Sumoharjo village. The research method uses multiple linear regression analysis. The research area was taken purposively, namely in the village of Urip Sumoharjo, Pohjentrek Subdistrict, Purworejo District, Pasuruan City. The method for taking samples from respondents is Accidental Sampling. Samples were taken from 61 consumers at Mrs. Nur Jannah's UMKM. The data taken is primary data and secondary data using interview techniques, observation, and filling out questionnaires for respondents. The research results show that consumer characteristics based on age at the age of 26 to 35 years are 42.6%. Characteristics of respondents based on education level, namely at the high school level, was 65.6%. The largest characteristic of respondents based on gender is women with 62.3%. And from the F test, X1, X2, X3, And in the T test all X variables have a significant influence on variable Y because they are smaller than 0.05.Kata kunci: Consumer Prefernces, Consumer Characteristics.